Da enciclopédia enquanto um círculo que se fecha à Wikipédia enquanto uma rede que abre: um gesto interpretativo - Scotta, Larissa (2008)
In this research we promote a reflection about the passage that we believe to exist from an (illusory) totality of knowledges discursively constructed in encyclopedias regarding versions spatially limited of this technological instrument to an impossibility of construction of this totality on Wikipedia virtual site, considered for many subjects as the complete encyclopedia . From an intermediate theoretical position between French Discourse Analysis and History of Ideas, we believe that, even though a discourse about the Wikipedia circulates signifying it as the encyclopedia where the numerical totality of knowledges could be stored , due to Wikipedia to be open to collaborative edition and to introduce itself as a indefinitely open net, make impossible any attempt of apprehension of all . In order to problematize around these questions, initially, we give a brief overview concerning of total knowledge utopia found in fullness on the Library of Alexandria, for the reason what we understand that such utopia is constitutive of the imaginary about encyclopedia. After this overview, we looked for understanding what is being considered as an encyclopedia in the course of time. Following, we focus the Wikipedia and the discourse that circulates about it. Bearing in mind what we discussed with reference to what an encyclopedia is and about the Wikipedia configuration, we propose to deem the encyclopedia as a closed circle and the Wikipedia as an open net.